Mild-moderate alcohol consumption and diabetes are associated with liver fibrosis in patients with biopsy-proven MASLD - Huang, Ang; Zou, Cailun; Dai, Zhe; Sun, Ying; Wang, Jing; Liu, Shuhong; Han, Lin; Chen, Songhai; Liang, Qingsheng; Wang, Chunyan; Zhuang, Yingjie; Dang, Tong; et al. (Frontiers in Pharmacology, 2024)
Background: It is unclear whether patients with metabolic dysfunction-associated steatotic liver disease (MASLD) are allowed variable low levels of alcohol. This study aimed to evaluate the effect of mild-moderate alcohol consumption on the biochemical and histological characteristics of patients with MASLD. Methods: Alcohol consumption was assessed in 713 patients with MASLD who underwent liver biopsy. Non-drinking, mild-moderate drinking, and excessive drinking were defined as 0 g/day, 1-<20 g/day, and >20 g/day for women and 0 g/day, 1-<30 g/day, and >30 g/day for men, respectively. Liver biopsies were scored according to the NASH CRN system. Results: A total of 713 participants (median age 39.0 years and 77.1% male) with biopsy-proven MASLD were enrolled, including 239 nondrinkers, 269 mild-moderate drinkers and 205 excessive drinkers. Excessive drinking was associated with increased risks for lobular inflammation and liver fibrosis compared to nondrinkers and mildmoderate drinkers. Compared with non-drinkers, mild-moderate drinkers had significantly lower odds for steatosis (OR = 0.60, 95% CI = 0.38-0.93, p = 0.025), hepatocellular ballooning (OR = 0.52, 95% CI = 0.29-0.91, p = 0.020) and fibrosis (OR = 0.50, 95% CI = 0.31-0.81, p = 0.005). However, in non-excessive drinkers with type 2 diabetes mellitus (T2DM), there was no association between mild-moderate alcohol consumption and liver fibrosis (OR = 0.562, 95% CI = 0.207-1.530, p = 0.257). Conclusions: Mild-moderate alcohol consumption might be protective against liver fibrosis in MASLD patients, which is modified by the presence of T2DM. However, further longitudinal studies are needed to determine the effect of ongoing alcohol consumption on disease severity.